Experimental Research on Wind-Cooling Quenching of 20Mn2CrSi Steel. Issue 3 (April 2021) - Fan, Z.Y.; Li, X.J.; Liang, X.; Luo, P.; Lin, X.Y.; An, W.C.; Sun, L.Z.; Shi, Y.Z.; Yang, T.; Chen, R.Z.
Abstract: Compared to aluminum alloy wheels, steel wheels have been widely used in the automobile industry due to the low cost and high plasticity and toughness. In this report, wind-cooling quenching of the wheels made of 20Mn2CrSi steel is studied. The CCT curves of 20Mn2CrSi are firstly drawn based on the thermal expansion experiment. Then the samples with different thicknesses (4mm, 6mm, 11mm) are tested under air cooling and wind cooling conditions to find out their optimum transfer time of quenching, and the cooling rates of the surfaces and internal of the sample under wind-cooling condition. The Vickers hardness of the samples after wind-cooling quenching are also measured by a Vickers hardness meter. The results show that the cooling rate is slow when the air volume during cooling is 900m3/h, making the hardness of the samples fail to meet the use standard. Therefore, in order to improve the cooling rate and reduce the thermal stress and structural stress during quenching, water atomization quenching method is proposed, which can provide a certain reference value for the quenching process of 20Mn2CrSi steel wheels.